2014
DOI: 10.1074/mcp.m113.036442
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal Proteomics and Ribosome Profiling Provide a Comprehensive View of the Alternative Translation Initiation Landscape in Mice and Men

Abstract: Usage of presumed 5UTR or downstream in-frame AUG codons, next to non-AUG codons as translation start codons contributes to the diversity of a proteome as protein isoforms harboring different N-terminal extensions or truncations can serve different functions. Recent ribosome profiling data revealed a highly underestimated occurrence of database nonannotated, and thus alternative translation initiation sites (aTIS), at the mRNA level. Nterminomics data in addition showed that in higher eukaryotes around 20% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
166
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 125 publications
(182 citation statements)
references
References 106 publications
11
166
0
3
Order By: Relevance
“…This is the case with the human PRKAA1 gene for which the synthesis of a truncated proteoform has been validated previously at the protein level 15, 22. Figure 2A and B shows ribo‐seq data and mRNA‐seq data aligned to the first exon of the human PRKAA1 gene and the mouse Prkaa1 gene, respectively.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…This is the case with the human PRKAA1 gene for which the synthesis of a truncated proteoform has been validated previously at the protein level 15, 22. Figure 2A and B shows ribo‐seq data and mRNA‐seq data aligned to the first exon of the human PRKAA1 gene and the mouse Prkaa1 gene, respectively.…”
supporting
confidence: 55%
“…While useful, these techniques suffer from high levels of signal noise, for example, elongating ribosomes pausing at particular codons 19, 20. Therefore, the use of ribo‐seq data is particularly powerful in combination with other techniques, for example, phylogenetic approaches 10 or MS 21, 22, 23.…”
mentioning
confidence: 99%
“…From wholeproteome or acetylome analysis, they are hardly ever found (Lee et al, 2012;Menschaert et al, 2013;Vanderperre et al, 2013; M.S. Van Damme et al, 2014;Wilhelm et al, 2014). However, when all 27,168 Arabidopsis proteins were analyzed, 620 were found to start with MM, representing over 2% of all encoded proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Recent global mapping of ribosome binding sites in mammals revealed that translation initiation is more versatile and alternative translation is more prevalent than previously imagined (Lee et al, 2012;Menschaert et al, 2013;Vanderperre et al, 2013; M.S. Van Damme et al, 2014;Wilhelm et al, 2014). Such mechanisms can vastly expand the diversity of the proteome and provide greater versatility for the encoded proteins.…”
Section: Introductionmentioning
confidence: 99%
“…For example, numerous small upstream ORFs (uORFs) have been identified whose translation might regulate expression of the main ORF. Ribosome profiling has also revealed a wealth of events in which translation is initiated at alternative start codons 3 (triplets of nucleotides other than the triplets at which translation is normally assumed to initiate), and read-through events 4 in which translation continues beyond the stop codon (the nucleotide triplet at the end of the ORF). Not only do these two types of event increase the overall diversity of proteoforms (molecular forms of proteins produced from genes) 5 , but they have also emerged as regulatory mechanisms for hundreds of genes in eukaryotic genomes.…”
mentioning
confidence: 99%